PENGARUH KONSENTRASI KAPUR (CaCO3) TERHADAP PERTUMBUHAN LOBSTER AIR TAWAR (Cherax quadricarinatus) - Arki Y. Arsono; Rustadi Rustadi; Bambang Triyatmo (Jurnal Perikanan Universitas Gadjah Mada, 2010)
This research was conducted to determine the effect of lime (CaCO3) concentration on the availability of calcium in water and growth of Crayﬁsh (Cherax quadricarinatus). Completely random design was used in the experiment that consisted of 4 treatments and 3 replications. Four treatments of lime concentration were 0, 50, 100, and 150 mg CaCO3/l. The research was conducted in Fisheries Research Station, Agriculture Faculty, Gadjah Mada University for 30 days. Ten Crayﬁsh were reared in 60 cm x 40 cm x 50 cm aquarium in 60 l water. Crayﬁsh were fed ad libitum with Tubifex tubifex. Calcium concentration on water, Crayﬁsh growth, and water quality were observed every tenth days. The data of calcium concentration on water and Crayﬁsh growth were analyzed with regression and correlation analysis at 95% conﬁ dence level, whereas water quality analyzed descriptively. The research showed that there was correlation between lime concentration and its availability in the water. It showed that, more lime concentration resulted on higher calcium availability in water. Crayﬁsh growth was relative faster on higher lime concentration.